Optimal contracts in a dynamic costly state verification model - Cyril Monnet; Erwan Quintin (European Central Bank (ECB), 2002)
This paper describes optimal contracts in a dynamic costly state verification model with stochastic monitoring. An agent operates a risky project on behalf of a principal over several periods. Each period, the principal can observe the revenues from the project provided he incurs a fixed cost. We show that an optimal contract exists with the property that, in each period and for every possible revenue announcement by the agent, either the principal claims he entire proceeds from the project or promises to claim nothing in the future. This structure of payments enables the principal to minimize audit costs over the duration of the project. Those optimal contracts are such that the agent's expected income rises with time. Moreover, except in at most one period, the principal claims the entire returns of the project whenever audit occurs. We also provide conditions under which all optimal contracts must satisfy hese properties
Keywords: D8; C7; 330; Costly State Verification; Dynamic Contracts; Monitoring; Theory of Uncertainty and Information